Effectiveness of Murabahah-Based Business Capital Financing at PT. BPRS Puduarta Insani - Ningsih, Sri Rahayu; Tri Inda Fadhila Rahma; Fauzi Arif Lubis (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Business capital financing is one type of financing offered to help business owners obtain funds to develop their business. In this scheme, BPRS Puduarta Insani acts as a representative to purchase goods from third parties and sell them to customers at a predetermined profit margin. The research method used is descriptive qualitative with a case study approach. Data was collected through direct interviews with three customers who received murabahah financing, as well as documentation and field observations. The research results indicate that the implementation of murabahah contracts at BPRS Puduarta Insani is in accordance with Sharia principles and established procedures. Based on five effectiveness indicators—Sharia compliance, return rate, financing quality, customer satisfaction, and target accuracy—it can be concluded that this financing is quite effective. However, there are still external challenges such as fluctuations in business income and low sharia financial literacy, which affect the smooth repayment of installments by some customers. Therefore, improvements in education and flexibility in the financing scheme are needed to further enhance effectiveness.